Prevalence and Risk of Nutritional Problems among Toddlers in Balikpapan, Indonesia: A Cross-sectional Study - Tanti Asrianti; Siswanto Siswanto; Irfansyah Baharuddin Pakki; Khumairotul Zahroh Al Ahmadi; Akhmad Dzikri (Pancasakti Journal Of Public Health Science And Research, 2025)
Nutritional challenges during early childhood remain a pressing global concern that significantly influence a country’s Human Development Index. This study aimed to assess the prevalence and risk of undernutrition-related health problems among toddlers in Balikpapan City, East Kalimantan Province. Using a descriptive-analytic design with a cross-sectional approach, data were collected from four integrated community health post (Posyandu) located across three sub-districts. The study population comprised toddlers attending Posyandu in West Balikpapan, Central Balikpapan, and South Balikpapan. A purposive sampling technique was applied based on predefined criteria, yielding a sample size of 78 toddlers. Findings revealed that from 78 toddlers, 11,5% toddlers were at risk of malnutrition, 20,5% toddlers were at risk of undernutrition, and 2,6% toddlers were at risk of stunting. These findings highlight the urgent need for targeted preventive interventions to address undernutrition risks in early childhood and offer valuable evidence to support regional health policy development. Prenatal interventions, including maternal supplementation and antenatal care are crucial. Exclusive breastfeeding remains essential but should be supported by broader strategies addressing complementary feeding and maternal conditions. Longitudinal studies are recommended to establish causal pathways.